A Preliminary Checklist of Fish Species in the Peat Swamp Forest of Ayer Hitam Utara State Park Forest, Johor, Malaysia - Muhammad Fahmi-Ahmad, Muhammad Fahmi-Ahmad; Muhammad Rasul Abdullah Halim, Muhammad Rasul Abdullah Halim; Mohd Lokman Ilham-Norhakim, Mohd Lokman Ilham-Norhakim; Muhammad Nur Azam Arshad, Muhammad Nur Azam Arshad; Zahar Azuar Zakaria, Zahar Azuar Zakaria; Intan Faraha A. Ghani, Intan Faraha A. Ghani; Mohamad Aqmal-Naser, Mohamad Aqmal-Naser; Siti Noratikah Mustafa, Siti Noratikah Mustafa; Muhammad Abu Bakar Abdul-Latif, Muhammad Abu Bakar Abdul-Latif; Mohammad Noor Azmai Amal, Mohammad Noor Azmai Amal; Amirrudin B. Ahmad, Amirrudin B. Ahmad; Khaironizam Md Zain, Khaironizam Md Zain (Pertanika, 2024)
Ayer Hitam Utara State Park Forest (AHUSPF) is an invaluable sanctuary in Johor, the last remaining intact peat swamp forest reserve that hosts many species unique to this distinctive habitat. Some rapid surveys conducted from 2019 to 2022 recorded 40 species of freshwater fish within AHUSPF. Notably, 11 are stenotopic to acid blackwater, and 12 are stenotopic to acid water, most belonging to the family Osphronemidae and Danionidae. The International Union for Conservation of Nature Red List has designated two species, Encheloclarias curtisoma and Betta persephone, as Endangered, while Betta omega is classified as Critically Endangered. The checklist presented herein was first produced from an inventory study in AHUSPF. The preservation of peat swamp forests in the area is under imminent threat due to the alarming rate of land conversion, forest fires, and the recent potential threat from the red-claw crayfish invasion in the aquatic environment. Hence, continuous monitoring is vital for documenting and updating the conservation status of the fish species. These endeavours will facilitate the development of practical conservation approaches to ensure the long-term sustainability of AHUSPF and its associated species.